Clinicopathologic Profile of Lung Cancer Patients at Murni Teguh Memorial Hospital in 2023 - Putri, Rosni Amanda; Lumongga, Fitriani; Permatasari, Amira; Laksmi, Lidya Imelda (Indonesian Journal of Cancer, 2025)
Background: Lung cancer is the most prevalent type of cancer worldwide, with a mortality rate of 1,817,469. This study aims to determine the clinicopathology of lung cancer patients in Murni Teguh Memorial Hospital.Methods: This is a descriptive study with a cross-sectional design. Clinical data were obtained from the medical records of lung cancer patients at Murni Teguh Memorial Hospital in 2023. The inclusion criteria were lung cancer patients who had been diagnosed histopathologically, while patients with incomplete medical records were excluded from the study. The data were processed using the Statistical Package for the Social Sciences (SPSS) software version 27.Results:  A total of 63 lung cancer patients were mostly (41.3%) aged 51-60 years. 48 subjects (76.2%) have been identified as male. Clinical symptoms of shortness of breath were found in 22 (34.9%) subjects, and the majority (47.6%) had a tumour size of T4. Based on histopathological classification according to WHO, 35 (55.5%) lung cancer patients mostly have adenocarcinoma.Conclusions: Lung cancer patients at Murni Teguh Memorial Hospital in 2023 presented with advanced disease, as reflected by the high proportion of large tumor size (T4) and respiratory symptoms such as shortness of breath. These findings highlight the tendency for late-stage presentation of lung cancer and underscore the need for improved early detection strategies and timely diagnostic interventions in this population.